Village as Contextual Factors and Other Risk Factors Related with the Incidence of Clinical Tuberculosis in Children in Wonogiri, Central Java: A Multilevel Analysis - Khairina Nur Hidayati; Bhisma Murti; Setyo Sri Rahardjo (Journal of Epidemiology and Public Health, 2024)
Background: Indonesia is in the second rank with the highest burden of tuberculosis (TB) in the world. Childhood is a period of rapid growth, the body still has a low immune system so it is susceptible to disease including tuberculosis in children which requires control efforts. This study aims to analyze the influence of risk factors and village contextual factors on the incidence of TB in children.Subjects and Method: Case-control study research was conducted in 82 villages in Wonogiri Regency, from November to December 2023. A sample of 200 children aged 0 to 4 years old was selected through fixed disease sampling. The dependent variable of this study was the incidence of TB in children. The independent variables in this study were stunting, contact history, exposure to cigarette smoke, home sanitation, gender, parental education, child age, parental income, BCG immunization status, and village contextual influences. Data on TB disease was obtained from the Tuberculosis Information System Application (SITB) at the Wonogiri District Health Service in 2023. Other data was collected through questionnaires. The data analysis was done through multilevel multiplelogistic regression.Results: The factors that increased the incidence of TB in children were stunting (OR= 10.94; CI 95%= 2.50 to 47.90; p= 0.001), contact history to TB (OR= 8.37; CI 95%= 1.60 to 43.83; p= 0.012), and exposure to cigarette smoke (OR= 7.36; CI 95%= 1.99 to 27.14; p= 0.003). The reducing factors were healthy sanitation (OR= 0.24; CI 95%= 0.08 to 0.78; p= 0.017), female children (OR= 0.40; CI 95%= 0.15 to 1.05; p= 0.062), and parents with ≥high school education (OR= 0.40; CI 95%= 0.15 to 1.05; p= 0.062). There was no relationship between age (OR= 0.93; CI 95%= 0.13 to 6.23; p= 0.940), parental income (OR= 1.14; CI 95%= 0.40 to 3.25; p= 0.807), and BCG immunization status (OR= 0.12; CI 95%= 0.00 to 105.98; p= 0.550). Village has a contextual influence on the incidence of clinical TB in children (ICC= 52.95%).Conclusion: The risk of clinical TB in children increased with stunting, a history of TB contact and exposure to cigarette smoke, it decreased with healthy home sanitation, female gender, parents with ≥high school education. There was no relationship between age, parental income, and BCG immunization status. The village has a contextual effect on the incidence of clinical TB in children.